Risk Analysis Applied to Industrial Refrigeration Installations that use Ammonia - Lopes, Toni Jefferson; Barros, Ricardo; Santos, Nara Lúcia dos; Costelli, Murilo Cesar; Silva, Adriano da; Cancelier, Adriano (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The toxic gas accidents as ammonia leaks can expose workers and the community, resulting from respiratory irritation or even death. The Primary Risk Analysis (PRA) may be used as a method to evaluate and qualify the potential for leaks in refrigeration systems. This research presents the results of a risk analysis simulation for a case study involving refrigeration facilities. The risk analysis study, as a methodology of environmental agencies for maintenance or obtaining environmental operating license establishments that produce or use toxic substances, is a valid method for the knowledge of the risks and possible effects of gas leaks with cloud formation toxic substances, such as ammonia. The risk analysis study resulted in the classification of the risk, the PRA and the vulnerability analysis with the modeling of gas clouds made by ALOHA software, with the use of leakage scenarios developed in the PRA. It was possible answers on the exposure of the risk of leakage of workers and the surrounding community, and the study of preventive and mitigation of accidents with this chemical agent.